Boundedness of Modified Fractional Integral Operators on Morrey Spaces. (January 2019) - Hazmy, Sofihara Al; Budhi, Wono Setia; Soeharyadi, Yudi
Abstract: We will show some properties of Modified Fractional Integral Operators, including the boundedness. There are two modified version that will be discussed. First, doesn't contain logarithm function, and second contains logarithm function.